Treatment Options in Congenital Missing Teeth - Seda Erken; Ömür Polat-Özsoy (Galenos Yayinevi, 2010)
The clinician is often encountered with missing teeth in orthodontic practice. In this review, clinical incidence, etiology and especially treatment options are described. Treatment options of the most common congenital missing lateral and premolar teeth are presented with advantages and disadvantages to provide a brief guide for daily practice.